Pregnancy after heart transplantation: a well‐thought‐out decision? The Quebec provincial experience – a multi‐centre cohort study. (26th March 2018) - Dagher, Olina; Alami Laroussi, Nassiba; Carrier, Michel; Cecere, Renzo; Charbonneau, Eric; de Denus, Simon; Giannetti, Nadia; Leduc, Line; Cantin, Bernard; Mansour, Asmaa; Poirier, Nancy; Raboisson, Marie‐Josée; et al.
Summary: Despite reports of successful pregnancies in heart transplant (HTx) recipients, many centers recommend their patients against maternity. We reviewed our provincial experience of pregnancy in HTx recipients by performing charts review of all known gestations following HTx in the province of Quebec (Canada), stratified between planned and unplanned pregnancies. Long‐term survival was compared to HTx recipient women of childbearing age who did not become pregnant. Eighteen pregnancies, 56% unplanned, occurred in eight patients, 10.1 (2.6–27.0) years after HTx. Immunosuppression was CNI‐based, with a mean dose increase of 48.3% (tacrolimus) and 26.5% (cyclosporine), without rejection. Cardiometabolic complications were high compared to the general Canadian population, including preeclampsia (15.4% vs. 5.5%), hypertension (38.5% vs. 4.6%), and diabetes (15.4% vs. 5.6%). Mean gestational age was 35.1 (23.4–39.6) weeks (72.2% live births; 53.8% prematurity). Mean birthweight was 2418 (660–3612) g. Serum creatinine increased during pregnancy, becoming significant after delivery ( P = 0.0239), and returning to preconception level in all but three patients within a year. After 4.6 (1.2–17.2) years of follow‐up, two rejection episodes occurred in one patient. Long‐term mortality was similar to overall HTx women (Kaplan–Meier; P = 0.8071). Pregnancy in HTx carries high cardiometabolic complications and decreased kidney function, but is feasible with acceptable outcomes and no impact on mother's survival.